POTENSI DAUN WARU DAN KULIT APEL SEBAGAI BAHAN AKTIF HAIR TONIC UNTUK MENGATASI RAMBUT RONTOK - Fitri Nur Hidayah; Erfa Kurnia Prastiwi; Fitriana Saputri; Rois Fatoni (JURNAL TEKNIK KIMIA VOKASIONAL (JIMSI), 2021)
The problem of hair loss is often underestimated, because it is considered normal and experienced by many people. Though the problem of hair loss should be watched out for. Most people today solve the problem of hair loss by using cosmetics on the market in the form of hair tonics. If used too often, the synthetic chemicals contained in it have the potential to cause damage to the hair and scalp. This requires natural ingredients such as hibiscus leaves and apple skin as active hair tonic ingredients. The purpose of writing this scientific article is to explore the potential of hibiscus leaves (Hibiscus tiliaceus L) and apple skin (Malus domestica) as hair tonic to treat hair loss. The writing method used is narrative review. Journals and articles obtained from online databases are compared and then analyzed to obtain results relevant to the purpose of scientific articles. The results of previous research on hibiscus leaves showed that the hair tonic formulation in testing the appearance and aroma had good information, was attractive and did not sting. Apart from that, it also meets the requirements in testing pH, homogeneity, stability and viscosity. Meanwhile, apple skin contains polyphenols which are active antioxidants with a power of 100 times more effective than vitamin C and 25 times higher than vitamin E and also able to strengthen hair roots and overcome dandruff. Utilization of hibiscus leaves and apple skin as active ingredients for hair tonic production is considered effective as a form of hair care to prevent hair loss.